Railway Bound: The CBRE, the ACCL and the Development of a National Working-Class Community, 1908-1930 - Sheffer, Warren James (Queen's University, 1997)
The 1920s is generally seen as a period of defeat for Canadian labour. With the rise of monopoly capital, strike activity and union membership steadily declined in the face of wage cuts, new technologies and corporate welfare schemes. The continental alliance of the American Federation of Labor (AFL) and the Trades and Labor Congress of Canada (TLC) that, for the most part, provided labour's leadership during this crisis, proved ineffective. By 1927 a secessionist movement challenged the legitimacy of the AFL/TLC alliance. In March of that year, the Canadian Brotherhood of Railroad Employees (CBRE), gathered with the One Big Union (OBU), the Canadian Federation of Labour (CFL), and communist-influenced unions, including the Mine Workers' Union of Canada and the Lumber Workers' Industrial Union, to form the All-Canadian Congress of Labour (ACCL). It is the focus of this thesis to bring the Congress front and centre and to provide an alternative interpretation of its effort to build a national labour movement in the 1920s--one that was neither opportunistic, anti-communist, nor right-wing. Instead, this thesis supports the contention that the ACCL was a counter-hegemonic, working-class initiative that aimed to improve the political representation and material conditions of the Canadian worker.
Keywords: Canadian Brotherhood of Railway, Transport and General Workers -- History